Amino acid based hydrazones: synthesis and evaluation as new chemosensors for ion recognition - Esteves, Cátia I. C. (2013)
Anionic and cationic species are key players in biological, environmental, and chemical processes and there is an interest in the design of artificial receptors for molecular recognition studies. Optical receptors are preferred due the possibility of using low cost and widely available instruments, and consist of a reporting unit, able to change its fluorescence or absorption properties, and a binding unit, for the selective recognition of the anionic/cationic substrate. Colorimetric chemosensors allow a straightforward “naked-eye” detection, whereas fluorescent chemosensors are more sensitive and versatile, offering subnanometer spatial resolution.1 Metallic cations can be complexed through N, O and S donor atoms as in amino acids, at the main and side chains, and in aromatic heterocycles, which are most usually fluorophores. Therefore, the insertion of suitable heterocyclic systems at the side chain of natural amino acids can add extra functionality to the amino acid.2 Anion coordination is based on hydrogen bonding and electrostatic interactions and at amino acids these processes can arise from side and main chain OH and NH groups, whereas in heterocycles the presence of NH groups or suitable substituents such as urea and thiourea groups can provide a site for coordination.3 Therefore, the combination of the above mentioned entities would result in a ditopic system capable of detecting both anions and cations. Bearing in mind our research on the synthesis and application of colorimetric/fluorimetric probes for anions and cations based on heterocycles and amino acids,4 we now report the synthesis of novel hydrazones based on a phenylalanine core (Figure 1). The evaluation of the new amino acid hydrazones as fluorimetric chemosensors was carried out by performing spectrofluorimetric titrations in acetonitrile and in aqueous solutions, in the presence of relevant organic and inorganic anions, and of alkaline, alkaline-earth and transition metal cations. 1H NMR titrations were also conducted in order to gain further insight into the site and mechanism of coordination for anions and cations.